The incredible boong gi: Educational game RPG for mathematical understanding ability - Setiyani Setiyani; Sri Sumarwati; Laela Sagita; Dzaki Fadhlurrohman (International Journal of Education and Learning, 2021)
Some of the android-based mobile game genres that are currently very popular such as adventure, first-person shooter, fighting, racing, and others. This development should provide opportunities in the field of education to make games not only for fun but also for education. The purpose of this study was to produce educational games that were valid, practical, and had potential effects to improve the mathematical understanding of the relationship and function of junior high school students. The research method used is RD (research development) using the ADDIE model. The data collection techniques used were documentation, interviews, and tests of mathematical comprehension abilities. The results obtained from the game "The Incredible Boong Gi" are valid with an average of 96.70% of expert validators and media validators. The results of the practicality questionnaire from 9 students averaged 90.32%. The results of data analysis show that educational RPG games have valid, practical criteria and have potential effects. RPG games are valid in terms of relevance, systematics, student-centered compatibility, game design, and compatibility. RPG games get practical results from implementation in small groups. Furthermore, the educational RPG prototype has the potential effect of improving students' mathematical understanding abilities. RPG games provide a fun learning atmosphere, by playing students can also learn. Making RPG games is also not difficult, according to the competence of students to be achieved and challenges the creativity of the teacher.